The Authority of Knowledge and Teacher-Student Relations: An Epistemological Analysis of Islamic Education Based on Kitab Kuning - Didin Didin; Tohirin Tohirin; Basirin Basirin; Sumadi Sumadi (Lembaga Yasin AlSys, 2026)
Amid contemporary information disruption that tends to de-authorize teachers and fragment epistemic authority, pesantren (Islamic boarding school) traditions persist as a distinctive model of knowledge transmission grounded in the classical pedagogy of Kitab Kuning (Yellow Book). This study philosophically dissects the epistemological construction of scholarly authority and the dynamics of teacher–student relations within this tradition. Using a qualitative–descriptive approach framed by the Islamic philosophy of science, it analyzes the classical texts Ta’lim al-Muta’allim and Adab al-‘Alim wa al-Muta’allim. The findings show that Islamic scholarly authority is not rooted in power dominance but in the legitimacy of transmission through sanad (chain of narration), which functions as an epistemic anchor for the authenticity and continuity of knowledge. Epistemologically, teacher–student relations integrate a triadic mode of reasoning: bayani (textual authority), burhani (logical validation), and irfani (spiritual intuition), positioning the teacher’s authority as an epistemic guarantee that safeguards the originality of meaning and the barakah (blessing) of knowledge. The study concludes that this classical construction of authority and relational ethics offers a critical corrective to modern educational tendencies that marginalize spiritual depth and intellectual humility, and implies the need to revitalize the concept of adab in contemporary Islamic higher education to counter the shallowing of intellectual spirituality.